2012
DOI: 10.1016/j.cattod.2012.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Salophen and salen oxo vanadium complexes as catalysts of sulfides oxidation with H2O2: Mechanistic insights

Abstract: a b s t r a c tThe application of V(V) catalysts in oxidation of sulfides with peroxides offers an efficient procedure, that is compatible with different functional groups, and leads to good yields and selectivities. However, the understanding of the factors affecting the reactivity of different catalysts is still far to be complete. An experimental and theoretical study on a series of V(V) complexes containing variously substituted salen and salophen ligands is reported with the aim to correlate the activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…In agreement with this, theoretical calculations showed that salophen complexes reasonably react in a planar conformation, while the salen vanadyl hydroperoxo active species is more stable in a bent structure [9].…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…In agreement with this, theoretical calculations showed that salophen complexes reasonably react in a planar conformation, while the salen vanadyl hydroperoxo active species is more stable in a bent structure [9].…”
Section: Introductionsupporting
confidence: 67%
“…In fact, vanadium is currently used, mainly in its pentoxide form, to catalyze a number of industrial production processes or as a strengthening agent in alloys [8]. Inspired by the coordination chemistry of natural systems, among a wide range of synthetic ligands, vanadium has been successfully used to form stable complexes with salen and salophen ligands both in its IV and V oxidation states [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations